Report of the 42nd annual conference held in The Central Hall, Westminster, June 14th to 18th, 1943. - Labour Party (London : Labour Party, 1943)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Labour Party; Wereldoorlog 2; Groot-Brittannië.